Methyl 3,4-Dihydroxybenzoate Induces Neural Stem Cells to Differentiate Into Cholinergic Neurons in vitro - Pan, Jun-Ping; Hu, Yang; Wang, Jia-Hui; Xin, Yi-Rong; Jiang, Jun-Xing; Chen, Ke-Qi; Yang, Cheng-You; Gao, Qin; Xiao, Fei; Yan, Li; Luo, Huan-Min (Frontiers in Cellular Neuroscience, 2018)
Cholinergic neurons are one of the important cell types of the CNS, which includes the brain, cerebellum, spinal cord, and the peripheral nervous system. Neural stem cells（NSCs）have been shown as a potential source for replacing degenerated neurons in neurodegenerative diseases. However, the therapeutic potential of these cells is limited by the lack of effective methodologies for controlling their differentiation. Inducing endogenous pools of NSCs by small molecule can be considered as a potential approach of generating the desired cell types in large numbers. Here, we demonstrated that Tuj1 positive cells（immature neuron）are increased, GFAP positive cells（astrocyte）are inhibited by a small molecule（Methyl 3,4-dihydroxybenzoate; MDHB）in the differentiation of NSCs. Tuj1 positive cells can differentiate to MAP2 and NeuN positive cells（mature neuron）after MDHB treatment. Moreover, we found that the majority of MDHB-induced neurons were immunopositive for cholinergic neurons marker ChAT and motor neurons marker Isl1, and it significantly expressed synapsin 1（SYN1）and postsynaptic density protein 95 (PSD-95) . Studies on the mechanisms revealed that MDHB regulated the fate of NSCs by inhibiting AKT phosphorylation and activating autophosphorylation of GSK3β at tyrosine 216, which led to β-catenin degradation and abolishment of entering the nucleus. Therefore, it regulated the expression of cell cycle-related gene and cholinergic neurons-related gene. Collectively, this report provides the strong evidence that MDHB promotes NSCs differentiation into cholinergic motor neurons by regulating cell cycle and the cholinergic neuronal differentiation Isl1 gene with GSK3β, and it may provide a basis for pharmacological effects directed at NSCs.